Development of multimedia-based learning media interactive on a subject of cooling systems in Vocational School of Industry Yogyakarta - Amirudin Amirudin; Setuju Setuju (Jurnal Taman Vokasi, 2018)
This study aims to produce cooling system learning media in an easy way to operate and suitable to be used in teaching and learning activities. This type of research was Research and Development with the procedure of developing the media through 10 stages. The technique of collecting data used the validation sheet. The data analysis technique used quantitative analysis. The result of the media expert validation shows that the flash-based cooling system learning media is feasible with an average of 96.4% which included three aspects of assessment, namely: aspects of media display, use of images, sound and evaluation questions, and navigation systems. The result of the material expert validation showed that the learning media of flash-based engineering images was very feasible with the average of 85.4% which included three aspect of assessment, namely: aspects of material relevance, an aspect of learning materials content, and aspect of multimedia ease of operation. The results of user evaluations indicate that flash-based cooling system learning media was very feasible, with the percentage of 84.5% in small group trials and 82.6 in large group trials covering 5 aspects, namely: an aspect of material relevance, a content of learning materials, convenience operation, navigation menu, and system display design.